Предмет: Математика,
автор: nechaev79841023637
(X-3)(x+3)-(x-8)(x+8)
Ответы
Автор ответа:
1
(X-3)(x+3)-(x-8)(x+8)
х^2 + 3х - 3х - 9 - (х^2 + 8х - 8х - 64) = 0
х^2 + 3х - 3х - 9 - х^2 - 8х + 8х + 64 = 0
55 = 0.
Ответ: нет корней.
Удачи)))
х^2 + 3х - 3х - 9 - (х^2 + 8х - 8х - 64) = 0
х^2 + 3х - 3х - 9 - х^2 - 8х + 8х + 64 = 0
55 = 0.
Ответ: нет корней.
Удачи)))
Автор ответа:
1
Похожие вопросы
Предмет: География,
автор: rgubaev41470
Предмет: Алгебра,
автор: betonchi
Предмет: Математика,
автор: anjelikakim562
Предмет: Математика,
автор: МАК2006
Предмет: Математика,
автор: Volhkova191205